Psoriasis patients’ experiences concerning medical adherence to treatment with topical corticosteroids - Svendsen MT (Dove Medical Press, 2016)
Mathias Tiedemann Svendsen,1–3 Klaus Ejner Andersen,1–3 Flemming Andersen,1,3 Jakob Hansen,4 Anton Pottegård,5 Helle Johannessen6 1Department of Dermatology and Allergy Centre, Odense University Hospital, 2Centre for Innovative Medical Technology, Institute of Clinical Research, University of Southern Denmark, Odense C, 3Dermatological Investigations Scandinavia, University of Southern Denmark, Odense C, 4Leo Pharma, Ballerup, 5Clinical Pharmacology, Department of Public Health, University of Southern Denmark, 6Research Unit of User Perspectives, Department of Public Health, University of Southern Denmark, Odense C, Denmark Abstract: Nonadherence to topical treatment of psoriasis is a common cause of treatment failure. This focus group study was conducted to obtain the patients’ own experiences and explanations regarding medical adherence. The participants consisted of eight primary adherent patients with moderate psoriasis treated with corticosteroid or corticosteroid–calcipotriol combinations, purposefully sampled by age and sex at a dermatology outpatient clinic. Secondary medical adherence was supported by accessibility of the prescribing physician, the prescriber taking time to listen, having a more manageable disease, using a nonstaining product, and establishing routines around treatment at home. Secondary medical adherence was affected negatively by changes in daily routines, if the treatment influenced the patient’s sexual life, having too little time in the consultation room, lack of confidence in the prescriber, diverging information from health care personnel, experiencing side effects, having fear of side effects, impractical formulations of topical products, and impatience regarding time before an effect of the treatment was observed. From this study, the recommendations for the prescribing doctor to improve medical adherence are, the doctor needs to take time to listen to the patient, prescribe a topical product that is easy to apply and less greasy, inform the patients about benefits from treatments, and explain the rationale behind the treatment plan. Keywords: psoriasis, adherence, corticosteroids, calcipotriol, focus groups